2012
DOI: 10.1143/jpsj.81.053701
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity Induced by Bond Breaking in the Triangular Lattice of IrTe2

Abstract: IrTe 2 , a layered compound with a triangular iridium lattice, exhibits a structural phase transition at approximately 250 K. This transition is characterized by the formation of Ir-Ir bonds along the b-axis. We found that the breaking of Ir-Ir bonds that occurs in Ir 1Àx Pt x Te 2 results in the appearance of a structural critical point in the T ¼ 0 limit at x c ' 0:035. Although both IrTe 2 and PtTe 2 are paramagnetic metals, superconductivity at T c ¼ 3:1 K is induced by the bond breaking in a narrow range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
226
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(239 citation statements)
references
References 19 publications
9
226
4
Order By: Relevance
“…The results offer a novel electronic paradigm, in which localized charge-ordered states interact with conduction electrons introduced by the large SOC and the interplay between SOC and Coulomb interaction plays essential roles. Pd or Pt doping, introducing additional electrons, suppresses the charge order and the system becomes a superconductor at LT [11][12][13] . It indicates that the superconducting order competes with the charge order, similarly as in the cuprates 1-3 although the mechanism can be different, and suggests a possibility for realization of superconductivity involving the spin-orbit Mott state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results offer a novel electronic paradigm, in which localized charge-ordered states interact with conduction electrons introduced by the large SOC and the interplay between SOC and Coulomb interaction plays essential roles. Pd or Pt doping, introducing additional electrons, suppresses the charge order and the system becomes a superconductor at LT [11][12][13] . It indicates that the superconducting order competes with the charge order, similarly as in the cuprates 1-3 although the mechanism can be different, and suggests a possibility for realization of superconductivity involving the spin-orbit Mott state.…”
Section: Discussionmentioning
confidence: 99%
“…Further, if the localized Mott state interacts with itinerant conduction electrons, the system possibly experiences valence fluctuations as in the 4f rare-earth materials 10 and exhibits unprecedented physical phenomena. IrTe 2 was reported as a new CDW material with a modulation vector q ¼ (1/5 0 1/5) below a CDW transition temperature T C B260 K and also as a mother compound of Ir based superconductors [11][12][13] . Various efforts have been conducted to elucidate electronic mechanisms of the charge modulation 11,13,14 , but the CDW like nature was disputable.…”
mentioning
confidence: 99%
“…[1][2][3][4] Also the multi-band structure of the Fe 3d orbitals play important roles in superconductivity and magnetism of Fe pnictides and chalcogenides such as LaFeAsO 1Àx F x . 5) Recently, Pyon et al 6) and Yang et al 7) have discovered interesting interplay between lattice distortion and superconductivity in triangular lattice IrTe 2 in which multi-band Fermi surfaces are expected to play significant roles. Since the large spinorbit interaction of Ir 5d electrons is expected to entangle the spin and orbital degrees of freedom in IrTe 2 and the derived superconductors, Yang et al pointed out that the IrTe 2 system provides a new playground to explore and/or realize topological quantum states, which are currently attracting great interest in physics community.…”
mentioning
confidence: 99%
“…8) When the lattice distortion is suppressed by chemical substitution of Pt or Pd for Ir or intercalation of Pd, IrTe 2 becomes superconductors. 6,7) An electron diffraction study by Yang et al 7) observed the superlattice peaks with wave vector of q ¼ ð1=5; 0; À1=5Þ below the structural transition temperature. Such superstructure can be explained by charge density wave (CDW) driven by perfect or partial nesting of multi-band Fermi surfaces.…”
mentioning
confidence: 99%
“…In recent times, IrTe 2 has attracted considerable interest because of its peculiar structural/electronic phase transition and the emergence of superconductivity upon chemical doping 1,2) or intercalation. 2,3) IrTe 2 crystallizes in a trigonal CdI 2 -type structure with the space group P " 3m1 (No.…”
mentioning
confidence: 99%